Effect of Natural Dye Sensitizers towards the Improvement of Dye-Sensitized Solar Cell (DSSC) Efficiency - Hamid, NNA; Suhaimi, S; Yatim, NM (Amer Inst Physics, 2024)
Dye-sensitized solar cell (DSSC) get recognized due to ability in converting solar energy into electricity by using organic and inorganic materials. Also, society's demand on the sustainable green environment makes DSSC as the best candidates for developing solar devices that flexible, low cost in production and environmental friendly. This research extracts natural sensitizers from avocado peel, blueberry and pomegranate that immersed in the ethanol. It will use in the fabrication of DSSC as a photons absorbent. Apart from that, the dyes are undergoing the characterization analysis using Fourier transform infrared spectroscopy (FTIR) and ultraviolet-visible spectroscopy (UV-Vis) to observe the optical properties. As a result, the graph from FTIR shows the pattern of absorbance of dyes. Whereas, UV-Vis graph provides maximum absorption peak as well as energy band gap information which are for avocado peel is 665 nm with 1.87 eV, blueberry is 540 nm with 2.30 eV and pomegranate has wavelength of 530 nm with 2.34 eV. In addition, the efficiency of natural sensitizers for avocado peel, blueberry and pomegranate are collect which are 48.25x10(-12)%, 24.62x10(-12)% and 15.75x10(-12)% respectively.